Longer Operative Time Is Independently Associated With Surgical Site Infection and Wound Dehiscence Following Open Reduction and Internal Fixation of the Ankle. Issue 2 (April 2020) - Gowd, Anirudh K.; Bohl, Daniel D.; Hamid, Kamran S.; Lee, Simon; Holmes, George B.; Lin, Johnny
Background: Little is known regarding the association of operative time with adverse events following foot and ankle surgery. This study tests whether greater operative time is associated with the occurrence of adverse events following open reduction and internal fixation (ORIF) of the ankle. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was queried for cases of ankle ORIF (primary CPT codes 27766, 27769, 27792, 27814, 27822, 27823) performed during 2005-2016. Operative time was tested for association with the occurrence of adverse events with controls for baseline characteristics and primary CPT code. Results: A total of 20 591 procedures met inclusion/exclusion criteria. The average (±SD) operative time was 75.7 (±37.3) minutes and varied by baseline characteristics and primary CPT code. After controlling for these factors, a 15-minute increase in operative time was associated with an 11% increase in risk for developing surgical site infection (SSI; relative risk [RR]: 1.11; 95% CI: 1.06-1.16), 20% for wound dehiscence (RR: 1.20; 95% CI: 1.11-1.29), 10% for anemia requiring transfusion (RR: 1.10; 95% CI: 1.04-1.17), 60% for cerebrovascular accident (RR: 1.60; 95% CI: 1.17-2.18), 14% for unplanned intubation (RR: 1.14; 95% CI: 1.03-1.26), and 7% for extended length of hospital admission (RR: 1.07; 95% CI: 1.05-1.09). Conclusion: Operative time is linearly and independently associated with the risks for SSI, wound dehiscence, and other adverse events following ORIF of the ankle. Efforts should be implemented to safely minimize operative duration without compromising the technical components of the procedure. Levels of Evidence: Therapeutic, Level IV